2016
DOI: 10.1111/1751-7915.12432
|View full text |Cite
|
Sign up to set email alerts
|

Actinobacillus pleuropneumoniae grows as aggregates in the lung of pigs: is it time to refine our in vitro biofilm assays?

Abstract: Summary Actinobacillus pleuropneumoniae causes porcine pleuropneumonia and forms biofilms in vitro on abiotic surfaces; however, presence of biofilms during infections has not been documented. The aim of this study was to use a species‐specific fluorescent oligonucleotide probe and confocal microscopy to localize A. pleuropneumoniae in the lungs of two naturally infected pigs. Actinobacillus pleuropneumoniae was detected by fluorescence in situ hybridization and observed to grow as aggregates (~30–45 μm) durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 14 publications
5
22
0
Order By: Relevance
“…However, in vitro and also ex-vivo (Yang et al, 2017 ) studies have to be supplemented with in vivo studies if the response of the immune system toward bacterial biofilm infections is investigated (Rumbaugh and Carty, 2011 ; Roberts et al, 2015 ). This was also recently demonstrated with references to porcine infections due to Actinobacillus pleuropneumoniea (Tremblay et al, 2017 ).…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…However, in vitro and also ex-vivo (Yang et al, 2017 ) studies have to be supplemented with in vivo studies if the response of the immune system toward bacterial biofilm infections is investigated (Rumbaugh and Carty, 2011 ; Roberts et al, 2015 ). This was also recently demonstrated with references to porcine infections due to Actinobacillus pleuropneumoniea (Tremblay et al, 2017 ).…”
Section: Introductionsupporting
confidence: 64%
“…However, as seen from the descriptions of infections in the present review (Figure 3 ) it is likely that all chronic porcine infections are the cause of biofilm formation as in humans (Donlan and Costerton, 2002 ; Costerton et al, 2003 ; Brady et al, 2008 ). This assumption has also been supported in porcine pneumonia due to Actinobacillus pleuropnumoniae (Tremblay et al, 2017 ).…”
Section: Discussionmentioning
confidence: 71%
“…Poly-N-acetylglucosamine (PGA) is one major component of biofilm formation, and respective PGA synthesis genes are located in the pga operon (Kaplan et al, 2004). Biofilms comprising bacterial aggregates embedded in host material were recently described in naturally infected pigs (Tremblay, Labrie, Ch enier, & Jacques, 2016).…”
Section: App In the Environment And Biofilmsmentioning
confidence: 99%
“…Previous studies have reported several techniques for the identification of Actinobacillus pleuropneumoniae such as ribotyping and restriction analysis of PCR(PCR-REA) (Jaglic et al, 2004), multiple PCR based on the omlA gene (Angen et al, 2008) and enzyme-linked immunosorbent assay (ELISA) using the recombinant ApxIA, ApxIIA, ApxIIIA, ApxIVA proteins and lipopolysaccharide (Shin et al, 2011;Sassu et al, 2017;Teshima et al, 2017). Tremblay et al (2017) developed an ApxIV probe which could specifically detect APP in the swine lung tissue.…”
Section: Discussionmentioning
confidence: 99%
“…But its major use was the detection of serum antibodies to Actinobacillus pleuropneumoniae and this assay was difficult to develop and apply for clinical test. Tremblay et al (2017) developed a effective fluorescence in situ hybridization way using an ApxIV probe for the detection of Actinobacillus pleuropneumoniae. This way could specifically localize Actinobacillus pleuropneumoniae cells within the lung tissue by using species-specific oligonucleotide probe.…”
Section: Discussionmentioning
confidence: 99%